Intersemiótica y estrategia polisensorial como apoyo para niños disminuidos psíquicos - Kraso, Katarzyna; Mazepa-domaga, Beata (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
Presentation and description of a method of work with psychic handicapped children through music, visual and corporal expression, within a intersemiotic and polisensorial strategy. A case study on intersemiotic methodology is added.